2014
DOI: 10.1136/bcr-2013-202167
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron administration together with parenteral nutrition to very preterm Jehovah's Witness twins

Abstract: Preterm twin sisters (monozygotic) were born at gestational age 27 weeks and 5 days with birth weights of 935 and 735 g. They were admitted to our neonatal intensive care unit for a period of 1 month. Their parents were Jehovah's Witnesses and refused blood transfusion for their preterm daughters. Subcutaneous erythropoietin and intravenous iron were given as a prophylactic to avoid anaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…CosmoFer (intravenous iron dextran) is a low-molecular-weight iron dextran that has been given to preterm neonates described in case reports and studies, with no adverse effects identified, and is Food and Drug Administration (FDA) approved in infants 4 months and older. 22 - 25 However, iron dextran has an FDA black box warning due to its association with anaphylactic reactions. Intravenous iron sucrose (Venofer, Vifor International), may have safety advantages 25 and is the current intravenous iron preparation we use in the Primary Children’s Hospital Hematology clinic (Yaish and colleagues, 2017, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…CosmoFer (intravenous iron dextran) is a low-molecular-weight iron dextran that has been given to preterm neonates described in case reports and studies, with no adverse effects identified, and is Food and Drug Administration (FDA) approved in infants 4 months and older. 22 - 25 However, iron dextran has an FDA black box warning due to its association with anaphylactic reactions. Intravenous iron sucrose (Venofer, Vifor International), may have safety advantages 25 and is the current intravenous iron preparation we use in the Primary Children’s Hospital Hematology clinic (Yaish and colleagues, 2017, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Although UK law gives patients the right to access treatment, case law has limited doctors' rights to impose treatment on conscious patients with mental capacity, so Jehovah's Witnesses can decline even lifesaving treatment and recently one died in front of doctors after refusing blood transfusion. 13 The picture has become complex with changing dynamics.…”
Section: Medicalisation In the Medical Literaturementioning
confidence: 99%